Measuring Stock Prices Through Earning per Share, Profitability, Solvability and Corporate Governance as Moderation Variables (Case Study on Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) 2015-2019) - Mondra Neldi; Nandan Limakrisna (Journal of Accounting and Finance Management, 2020)
This study aims to examine how much influence Earning Per Share, Profitability, and Solvability with Corporate Governance as a moderating variable. The population of this study was 71 companies listed on the Indonesia Stock Exchange (IDX) with a sample of 30 companies during 2013-2017. This study uses purposive sampling. The data analysis technique used in this study is multiple linear regression analysis.From this study the conclusions are as follows: Earning Per Share variable shows the results that have a positive and significant effect on stock prices, Profitability and Solvability shows no effect on Stock Prices, Earning Per Share which is moderated by Corporate Governance, Profitability moderated by Corporate Governance and Solvability moderated by Corporate Governance shows results that have no significant effect on stock prices. In further research, it is expected to be able to add independent variables to be able to explain what is the influence of the dependent variable, namely stock prices, and add all public companies to become research and replace the proxy of each variable to get better research results.